IDENTITAS BUDAK DI DUNIA MELAYU - . Anatona (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
Slaves emerged and were found in many places of the world including Malay. They existed in some ethnic-groups that settled in some areas in Sumatera and the Malay Peninsula. In fact, they had been integrated into the structure of the Malay society. This article aims to discuss one of the aspects of the slave identity that existed in Malay in the 19th century. The aspect which will be discussed is the characteristics based on symbols embedded in them.